2012
DOI: 10.1117/1.jbo.17.6.066010
|View full text |Cite
|
Sign up to set email alerts
|

Scanning-fiber-based imaging method for tissue engineering

Abstract: A scanning-fiber-based method developed for imaging bioengineered tissue constructs such as synthetic carotid arteries is reported. Our approach is based on directly embedding one or more hollow-core silica fibers within the tissue scaffold to function as micro-imaging channels (MIC). The imaging process is carried out by translating and rotating an angle-polished fiber micro-mirror within the MIC to scan excitation light across the tissue scaffold. The locally emitted fluorescent signals are captured using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…The necessity to monitor vascular graft endothelialization and maturation in real time during preconditioning has led our group to develop a fiber optic based (FOB) imaging system to accomplish this task [21], [22]. The imaging system is designed to noninvasively assess the graft endothelium without disturbing the graft during preconditioning in a bioreactor.…”
Section: Introductionmentioning
confidence: 99%
“…The necessity to monitor vascular graft endothelialization and maturation in real time during preconditioning has led our group to develop a fiber optic based (FOB) imaging system to accomplish this task [21], [22]. The imaging system is designed to noninvasively assess the graft endothelium without disturbing the graft during preconditioning in a bioreactor.…”
Section: Introductionmentioning
confidence: 99%
“…microscopy). We recently published a study that demonstrated the development of a novel imaging system utilizing miniature fiber optical devices for nondestructive, single-cell-level resolution imaging of bioengineered tissue constructs [47,48]. The current study demonstrates the ability to positively identify implanted GFP-MPCs and -ECs after 8 weeks implantation in vivo , a sufficiently long enough time to follow many regenerative processes.…”
Section: Discussionmentioning
confidence: 89%
“…Subsequently, we demonstrated the ability to image the interactions and differentiation capabilities of 3 fluorescently labeled cell types: MPCs, ECs and PCs, in real time in vitro , demonstrating a biological fluorescent imaging application. Combining the method developed here with the fiber-optic-based imaging modality described before [47,48], it will be possible to document tissue development and monitor the dynamic interplay between multiple cells types in vivo , in real-time, and with single-cell-level resolution. Such a technology may serve as a potent platform for testing the effects of different biological or pharmacological agents on tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…To realize the full potential of fluorescent proteins, however, one needs to go beyond the current framework for cell and tissue analysis, which is based on invasive tools such as immunohistochemistry and cell extraction for molecular assays such as Western blotting and quantitative Polymerase Chain Reaction (qPCR) [3,4]. Our imaging system allows non-invasive monitoring of bioengineered tissue constructs, through turbid and scattering media, while providing cell size (15-20 µm) resolution [5,6]. Additionally, the imaging system possesses a large working distance of 8 cm.…”
Section: Introductionmentioning
confidence: 99%